Unravelling the suitability of biological induction for halophilic lipase production by Halomonas sp. LM1C cultures. (September 2017) - Gutiérrez-Arnillas, Esther; Arellano, María; Deive, Francisco J.; Rodríguez, Ana; Sanromán, María Ángeles
Highlights: Triton X-100 induced Halomonas sp. LM1C lipase production. Staphylococcus equorum sp. AMC7 is a lipase inducer in Halomonas cultures. Inducer effect was maintained when operating in stirred tank bioreactor. Bioprocess kinetics was successfully characterized by fitting to logistic models. Abstract: In this study, the viability of using biological induction as an alternative to the conventional chemical induction in lipase production by a novel halophilic microorganism, Halomonas sp. LM1C, has been demonstrated. Thus, a 9-times increase of lipase activity (3000 U/L) was recorded when Staphylococcus equorum sp. AMC7 was present in the medium, which is competitive with the results obtained when Triton X-100 was added as chemical inducer. The GC–MS data allowed concluding the true nature of the biological inducer effect, as the existence of high percentages of isomeric forms of pentadecanoic acid were detected. The suitability of the proposed strategy was validated by operating at bench scale bioreactor, and the influence of bioreactor configuration on the biomass and lipolytic activity levels was studied. All the data were fitted to logistic and Luedeking & Piret models to characterize the bioprocess kinetics, concluding the growth-associated character of the produced lipolytic enzymes.